Exploring the psychology of children and young people's participation in organizations. [article]. - Yacat, Jay A.
A survey among 41 children and young people's organizations, and key informant interviews and discussions among 40 officers and members of 10 selected organizations in Metro Manila and Davao were conducted in order to map the nature and processes of youth participation in organizations. it was found that participation is shaped by three contexts: the organization itself; the adult-partner organization, and the community wherein the youth organization is located. Organizational mandate, size, and roles within the organization influenced the form and level of participation in the youth organization. Three models of facilitating participation by adult-partner organizations were identified. Acceptance by local communities of youth participation is a function of the approaches and strategies employed by the adult-partner organizations. -- (from the author)